With the best of intentions: a large sample test of the intention‐behaviour gap in pro‐environmental consumer behaviour. (26th June 2016) - Grimmer, Martin; Miles, Morgan P.
Abstract: Many consumers intend to make pro‐environmental purchases; however, this is not always what occurs. A gap exists between consumer intentions to purchase environmentally friendly products and their actual purchase behaviour. The current study uses a large sample of Australian consumers ( N = 772) to test Carrington, Neville and Whitwell's (2010) conceptual model of the intention‐behaviour gap. Responses showed that implementation intentions mediated the relationship between intention and pro‐environmental consumer behaviour. Behavioural control and environmental involvement were found to moderate the relationship between implementation intentions and behaviour. Shopping context was found to moderate the relationship between intention and implementation intentions. The findings have theoretical implications for furthering understanding of pro‐environmental consumer behaviour, and practical implications regarding how to generate socially beneficial behaviours.